HUBUNGAN ANTARA PERTUMBUHAN INDUSTRI, PERDAGANGAN INTERNASIONAL TERHADAP KONSENTRASI INDUSTRI DAN PERTUMBUHAN EKONOMI DI JAWA TIMUR - Santosa, Bambang Heru (Journal of Indonesian Economy and Business, 2006)
Objectives of the study is to analyze causal relationships among five variables. Thefirst three, development of industry influenced to the development of economy (economicgrowth), to concentration of industry, and to welfare. Second, concentration of industrypushed the economic growth. The third three, the international trade influenced toconcentration of industry, to economic growth, and to welfare. Finally, the impact ofeconomic growth to welfare.This analysis using structural equation modeling (SEM) and found that five of eightrelationships were significant and the rest were insignificant. First, development ofindustry negatively influenced concentration of industry. Second, international tradepushed concentration of industry. Third, concentration of industry also pushed economicgrowth. Fourth, international trade positively influenced economic growth. Finally, theeconomic growth positively influenced welfare. The development of industry wasinsignificant influence to the economic growth, and positively influenced to welfare. It isnegativite relation was caused by dispersion of the location of industry, so resulted loweconomies of scale. International trade was negatively influenced welfare.Policy implication obtained from the whole analyses, especially for the East JavaProvincial Government. In order to improve performance of the economy, it is suggestedemploying the Integrated Territory-provincial Planning based on comparative advantageamong regions.Keywords: industry; manufacturing; concentration; cultural regions; structural;Â Interdependency; territorial; integrated.